Regulamentação da terapia celular: uma análise comparativa dos modelos europeu, americano e brasileiro - Loureiro, Vitória Gimenes (2019)
Cell therapy has been highlighted in the scientific community due to its disruptive technological potential. This new therapeutic modality can significantly improve the way treatments are offered, as well as their clinical outcomes. However, scientific challenges, market obstacles and regulatory barriers need to be addressed in order to allow Cell therapy to reach its potential and, thus, meet the medical needs of the population. The present work consists in the presentation of an in-depth discussion on the European, American and Brazilian regulatory models, evidencing the general aspects of each sanitary regulatory system and specific regulatory framework that applies to Cell Therapy. The data presented were collected through extensive legal and bibliographic research. Comparative and critical analyses of the regulatory models of Cell Therapy studied identified key points that should be improved in the Brazilian regulatory model, such as: absence of an economic and objective analysis of the regulatory impact; rigidity of the standards, which can cause a stagnation of the sector; use of difficult comprehension language, which limits access and compromises the transparency of the norm; and regulatory inflation, which can create unnecessary bureaucratic obstacles.